2018
DOI: 10.1111/nph.15437
|View full text |Cite
|
Sign up to set email alerts
|

BES1 hinders ABSCISIC ACID INSENSITIVE5 and promotes seed germination in Arabidopsis

Abstract: Proper regulation of seed germination is essential for the successful propagation of a plant. The transcription factor ABSCISIC ACID INSENSITIVE5 (ABI5) of the abscisic acid (ABA) signaling pathway plays a central role in the inhibition of seed germination. ABI5 is precisely regulated by the core ABA signaling components and multiple other factors. However, the complex regulatory network of ABI5 remains largely unknown. In this study, we determined the biochemical interaction between ABI5 and the BRINSENSITIVE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 38 publications
3
44
0
Order By: Relevance
“…The ABA signaling pathway is a complex signaling network that integrates with other signaling pathways including BR, CK, JA, GA and auxin signals. Many studies have shown that ABI5, as a key positive transcription factor in the ABA signaling pathway, not only responds to ABA to regulate the expression of ABA-responsive genes, but also participates in the regulation of other plant hormone signaling pathways [10,33,41,42]. Components of auxin, CK, GA, JA and BR signals were shown to take part in ABI5 regulation or to be regulated by ABI5 [10,33,41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ABA signaling pathway is a complex signaling network that integrates with other signaling pathways including BR, CK, JA, GA and auxin signals. Many studies have shown that ABI5, as a key positive transcription factor in the ABA signaling pathway, not only responds to ABA to regulate the expression of ABA-responsive genes, but also participates in the regulation of other plant hormone signaling pathways [10,33,41,42]. Components of auxin, CK, GA, JA and BR signals were shown to take part in ABI5 regulation or to be regulated by ABI5 [10,33,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The brassinosteroid insensitive 2 (BIN2) kinase, a key repressor of brassinosteroid (BR) signaling, has been shown to phosphorylate and stabilize ABI5 during seed germination [9]. By contrast, the brassinazole resistant 1 (BZR1) and BR insensitive 1-EMS-suppressor 1 (BES1) transcription factors of the BR signaling pathway can suppress ABI5 transcriptional activity and promote seed germination in Arabidopsis [10,11]. Similarly, DELLA proteins of gibberellic acid (GA) signaling promote the transcriptional activity of ABI5 to inhibit seed germination and postgerminative growth, whereas the transcription factor inducer of CBF expression 1 (ICE1) interferes with the transcriptional function of ABI5 and promotes seed germination [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Further study has revealed that BES1 interacts with the bZIP domain of ABI5,hindering the association of ABI5 to its target promoters and suppressing the transcription of ABI5 downstream genes (Zhao, Dou, Gong, Wang, & Mao, 2019). Moreover, ABI3 and ABI5 form heterodimers and co‐regulate a series of genes (Nakamura, Lynch, & Finkelstein, 2001; Tezuka, Taji, Hayashi, & Sakata, 2013).…”
Section: General Relationship Between Br and Aba Pathwaysmentioning
confidence: 99%
“…At the TFs level, BES1 can repress ABI3 by recruiting TOPLESS and HDAC19 complex (Ryu et al ., ), and BZR1 can bind to the promoter of ABI5 to suppress its transcription (Yang et al ., ). Moreover, BES1 has been reported to directly interact with ABI5 to inhibit ABI5 binding to target gene promoters, therefore to promote seed germination (Zhao et al ., ).…”
Section: Introductionmentioning
confidence: 97%